The effect of azeotropic blended fuel on combustion characteristics in a ceiling vented compartment. (1st February 2017) - Ding, Yanming; Lin, Frank; Lu, Shouxiang; He, Qize; Wang, Changjian; Zhou, Ru
Highlights: Effects of azeotropic blended fuel pool fire are studied in a compartment. Four burning stages are divided by the temperature profiles intuitively. Q / Av 5/4 is applied to consider both the heat release rate and ventilation condition. Ghosting flame creates larger high-temperature regions and increases fire hazards. Azeotropism can effectively delay the appearance of ghosting flame. Abstract: The effect of azeotropic blended fuel on combustion characteristics was studied experimentally in a ceiling vented compartment. A variety of blended liquid fuels with different mixing ratios was employed to explore the thermal performances by the measurement of fuel mass loss rates, fuel and gas temperatures, etc. Results indicate that azeotropism has a significant effect during the combustion process, resulting in four typical burning stages, especially based on fuel temperature profiles: initial growth, azeotropic burning, single-component burning and decaying. Two significantly different thermal performances appear: steady burning (fuel-limited) and self-extinction (oxygen-limited). When the burning rate reaches a critical value, about 35 g m −2 s −1, the confined space cannot entertain enough air, self-extinction followed. A parameter ( Q / Av 5/4 ) derived from energy conservation equation is applied to divide the steady burning and self-extinction in consideration of both the heat release rate and ventilation condition, and the critical value is 200 kW/m 5/2 . Moreover, the ghosting flame maybe appears during the self-extinction condition, especially when Q / Av 5/4 > 300 kW/m 5/2 . The ghosting flame is detached from the fuel pan and goes from place to place with violent oscillation, which creates a larger high-temperature region and thus increases fire hazards. Meanwhile, according to both the fuel temperature profiles and mass loss rate, azeotropism can effectively delay the bulk boiling of the remaining single fuel and the emergence of ghosting flame.